(untitled) (Italian Review of Legal History, 2024)
This paper follows the crime of the politic defeatism from the first world war to the Fascism trough the 1926’ laws and the code processing. During the Great War in the October of 1917, one of the most difficult times for Italy, the Government introduced the crime of defeatism, next to the press censorship, a rule that was going to repress the freedom of expression of any citizen. The normative (D. Luog. n. 1561/1917, alias «decree Sacchi») suppressed not only news but also rumors about the war and politic propaganda against the war, especially the socialist one. The rule did not mention news and voices, but it used an indeterminate expression. Everybody, in the Parliament, in doctrine and jurisprudence, understood which were the goals to hit. Many citizens and politicians were convicted of defeatism. The Government was worried about the reaction of the citizens and of the soldiers in the face of war, difficulties and mournings. Also, it would not tolerate a public discussion about war. The crime of defeatism was part of the many measures that began to change the rule of law. Jurists and judges commented on the changes, with someone who assented to those. About limitations of freedom, repression of opinion crimes, control of public opinion, the judges had to balance freedom and national security, they often preferred the second one. The political opponents and the dissenting voices became enemies of the nation. After the war, returning to peacetime was exceedingly difficult. The discussion on the war did not finish and the Fascism used difficulties and frustration of Italians in its politics and for the rise to power. The Regime used the experience of the war, including violence, and the legislation in force during the war to eliminate freedom of expression. Two 1926’ laws, one on citizenship and the other of defense of the State, took up the letter and the spirit of the «decree Sacchi» for control of the propaganda against the Fascism by Italians abroad. Especially, in the law on the defense, which also reintroduced the death penalty, the voices were clearly sanctioned. After that, the repression of freedom of expression, exceptional during the war, became standard into the fascist legislation. The ideal was based on a special consideration of the war. Effectively, the Regime made the war one of the pivot points, giving it many meanings and active roles: the historical roots, the state-to-state relationships and the citizen-to-state one, the ideology of the penal code. The State rights were asserted against individuals, the political opponents began common criminals without political dignity, and the dissenting voices were repressed. The modern civilization was conceived as a continuous struggle between peoples of different countries, laws and rules to fight the enemies into and outside the borders were needed. This concept of civilization and of the State is clear in the crime of defeatism in the Fascist Penal Code. During the code processing the connection between war and Fascism, war and modern civilization, war and the duties of citizens, were constantly reaffirmed. In the project of the code, for the crime of defeatism the Minister of Justice Alfredo Rocco had maintained the sanction of news and voices, but he had extended the rule to all the citizens. He also had limited the application only «in wartime». The subjects called to participate in legislative processing identified the Great War as the root of the criminalization of the political opponents and the dissenting voices, they approved this heritage. Sometimes they suggested more severe punishment and a wider application, for instance in peacetime. The reasons why the Minister Rocco did not accept the proposed changes were not moderation: first, there were already a lot of tools to manage opposition and dissent (confinement, political police, Special Court for the Defense of the State) in peacetime; second, Rocco thought that the notion of wartime should be broad and not precisely defined. This rule, very authoritarian and indefinite, is still in force in our legal system.